Zhengtian Capsule versus flunarizine in patients with migraine: a multi-center, double-blind, double-dummy, randomized controlled, non-inferior clinical trial. Issue 1 (December 2016) - Cao, Kegang; Han, Fang; Lin, Anji; Yang, Wenming; Zhao, Jianjun; Zhang, Hui; Ding, Yanbing; Xie, Wei; Xu, Yinping; Yu, Tingmin; Wang, Xinzhi; Yang, Xiaosu; et al.
Abstract Background The primary objective of this study was to assess whether Zhengtian Capsule was non-inferior to flunarizine in efficacy and safety profile for prevention of migraine in adults. Methods This was a double-dummy, double-blind, multicenter, positive drug (flunarizine), parallel randomized controlled, non-inferior clinical trial. Patients (n = 360) were randomized in a 1:1 to receive either Zhengtian Capsule or flunarizine, including 12 weeks' intervention and 4 weeks' follow-up. The primary outcome measure was responder rate (defined as the percentage of subjects in a treatment group with 50 % or greater reduction in attack frequency during treatment compared with the baseline period). The secondary outcome measures included migraine attack frequency, the number of migraine days, pain evaluated by visual analogue scale (VAS) score, duration of migraine attacks, the times of using analgesics, patient-reported outcome (PRO) measure of migraine and the scores of short-form 36 Health Survey Scale (SF-36). Weight variation in both groups was also evaluated. Adverse events were monitored throughout the trial. Results Zhengtian Capsule was non-inferior to flunarizine in responder rate at week 12 and follow-up period (P = 0.002, P < 0.001). There was fewer migraine days in Zhengtian Capsule group at follow-up period compared with flunarizine (P = 0.001). For the total duration of migraine attacks, there was significant group difference at week 4 which favored the control group (P = 0.009). For the total score of PRO scale, there was statistical difference between the two groups at follow-up period (P = 0.021). There were also group differences between the two groups in the dimensions of somatization symptoms at week 4 (P = 0.022) and functional status at week 12 and follow-up period (P < 0.001, P < 0.001). However, there were no significant differences between the two groups in migraine attack frequency, VAS scores reduction, consumption of acute pain drugs and the dimension scores of SF-36 at any time interval of the treatment period (P > 0.05). No severe adverse events occurred in the trial. Flunarizine was found associated with a weight gain. Conclusion Zhengtian Capsule was non-inferior to flunarizine with regard to the primary endpoint. In addition, it could reduce migraine days and improve the functional status and somatization symptoms of migraine patients with good safety profile. Trial registration This trial was registered at Chinese Clinical Trial Register (ChiCTR), ChiCTR-TRC-13004412.